2018
DOI: 10.1080/00949655.2018.1450876
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis approaches to high-dimensional screening problems at low sample size

Abstract: Sensitivity analysis is an essential tool in the development of robust models for engineering, physical sciences, economics and policymaking, but typically requires running the model a large number of times in order to estimate sensitivity measures. While statistical emulators allow sensitivity analysis even on complex models, they only perform well with a moderately low number of model inputs: in higher dimensional problems they tend to require a restrictively high number of model runs unless the model is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Sample sizes of 20, 100 &1000 buildings for each method. SimStock (C1) Sobol' method, (C2) Derivative-based Global Sensitivity Measure (DGSM) (Becker et al, 2018), (C3) Elementary Effects (Morris Method) (Campolongo et al, 2007), 51 variable parameters in an urban district in North London. Each method evaluated at 10, 20 and 50 estimates.…”
Section: Sensitivity Analysis Methodsmentioning
confidence: 99%
“…Sample sizes of 20, 100 &1000 buildings for each method. SimStock (C1) Sobol' method, (C2) Derivative-based Global Sensitivity Measure (DGSM) (Becker et al, 2018), (C3) Elementary Effects (Morris Method) (Campolongo et al, 2007), 51 variable parameters in an urban district in North London. Each method evaluated at 10, 20 and 50 estimates.…”
Section: Sensitivity Analysis Methodsmentioning
confidence: 99%
“…Values close to one indicate strong agreement between the two rankings. ā€¢ Screening performance - Becker et al (2018) propose the number of parameters wrongly identified as influential as a fraction of the number of influential parameters as a test of the accuracy of screening. In this study, wrongly excluding influential parameters is considered less desireable than wrongly including non-influential parameters and so the fraction of false negatives is also calculated.…”
Section: Evaluating the Different Methods And Casesmentioning
confidence: 99%
“…ā€¢ Derivative based (DGSM) (Becker et al, 2018) -Similar to EER, this method uses a smaller increment.…”
Section: š‘‰ "mentioning
confidence: 99%
See 1 more Smart Citation
“…Another eminent challenge is that these emulation techniques usually work well when the problem at hand has a relatively low number of factors. But when the dimensionality of the problem is reasonably high, as in more complex models, emulators can become practically unsuitable for finding influential factors due to the curse of dimensionality and overā€fitting issues (Becker et al., 2018). Emulationā€based GSA suffers from two more drawbacks: (a) choosing the best emulator may not be easy due to the existence of a plethora of different emulators, and (b) some emulators also need adā€hoc experimental designs and specific arrangement of sample points for the sake of efficiency.…”
Section: Introductionmentioning
confidence: 99%